PENGARUH FASILITAS KERJA DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN KANTOR PERUMDA AIR MINUM TIRTA KELIMUTU KABUPATEN ENDE - Dila P, Anisa Ratna; Timuneno, Tarsisius; Maak, Clarce S (Universitas Nusa Cendana, 2023)
This study aims to find out the influence of Work Facilities, Work Motivation, and Work Productivity of Employees of the PERUMDA Tirta Kelimutu Drinking Water Office, Ende Regency, and to find out the Effect of Work Facilities and Work Motivation both partially and simultaneously on Employee Work Productivity of the PERUMDA Tirta Kelimutu Drinking Water Office, Ende Regency. This research is associative with a quantitative approach associated with taking a sample of 40 employees using a saturated sampling technique and collecting data through questionnaires, observation or interviews, and documentation. The data analysis technique used is a descriptive analysis using the continuum line method and inferential analysis using multiple linear regression models. The results showed with descriptive analysis show that work facilities are very high, so worker's motivation and work productivity are very high with very high achievements. The results of the hypothesis test with the t-test show that work facilities and work motivation have a positive and significant effect on the work productivity of the employees the PERUMDA Tirta Kelimutu Drinking Water Office. The results of the simultaneous test show that work facilities and work motivation simultaneously have a positive and significant effect on the work productivity of employees at the PERUMDA Tirta Kelimutu Drinking Water Office. Ensuring community well-being by providing access to clean water, it is crucial to prioritize the improvement of facilities and employee motivation in each department, particularly the technical team who work on-site. Therefore, PERUMDA Tirta Kelimutu Drinking Water, Ende Regency expected that it will always maintain high employee work productivity at the company and also provide appreciation in the form of awards and bonuses to employees who excel, as well as pay attention to the completeness of work equipment and equipment that may be inadequate to support work employees get better and employees are motivated to work optimally.